An environmental management industrial solution for the treatment and reuse of mussel wastewaters - Prieto Lage, Miguel A. (2015)
In the North-West of Spain, the annual production of mussel is 2×10 6 t (35% of the world). The industrial thermal treatment of mussels generates between 300 and 400L/t wastewaters that are continuously disposed into the sea without previous treatment and or further reuse. These effluents, relatively rich in organic matter (7g glycogen/L and 25g COD/L), contribute to the progressive deterioration of the marine ecosystem. We wish to suggest a biotechnological proce ss, based on a laboratory optimization and industrial pre-scale trials, to transform these industrial effluents into a growth culture medium to produce microbial biomass. Furthermore, this biomass is isolated and treated by different optimized separation and purification processes to produce several bioproducts: 1) single cell protein; 2) cell wall material with a high content in glucans and glycoproteins 3) fractions of 1,3-β-glucans and mannoproteins from yeast cell walls hydrolysis; and 4) a potential antioxidant extract. Finally, the authors propose a scaled process for its industrial application. In consequence, we believe that this work provides an environmentally friendly, eco-designed and profitable solution that allows integrating the mussel industry into the ecosystem in a sustainable way.